Pertumbuhan dan Hasil Sorgum di Tanah Latosol dengan Aplikasi Dosis Pupuk Nitrogen dan Fosfor yang Berbeda - Suminar, Ratna; ,, Suwarto; Purnamawati, dan Heni (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Sorghum (Sorghum bicolor L. Moench) is prospective crop for food as well as feed and bioenergy. It adapts to wide agroclimate and agroecology. However, the productivity is accounted low in Indonesia. Low productivity of sorghum can be enhanced through intensification, e.g., precise dose of nitrogen and phosphorus fertilizers application. The aim of this research was to determine the optimum dose of nitrogen and phosphorus fertilizers to maximize growth and yield of sorghum in latosol soil, in order to develop fertilizer recommendation on specific soil type. The research was conducted at Cikarawang, Bogor from March to July 2015. Nitrogen and phosphorus fertilizers were arranged and applied simultaneously using randomized completely block design with three replications. Nitrogen fertilizer was applied in five levels, i.e., 0, 60, 120, 180, 240 kg N ha-1 and phosphorus levels were 0, 18, 36, 54, 72 kg P2O5 ha-1. Results showed that the application of nitrogen and phosphorus fertilizers significantly increased vegetative growth and yield components. The optimum dose were 161 kg N ha-1 (133.7%) and 43 kg P2O5 ha-1 (121.5%) for latosol soil.Keywords: fertilizer, optimum dose, soil type, vegetative, yield component